The Impact of Information Technology on Academic Scientists' Productivity and Collaboration Patterns - Ding, Waverly W.; Levin, Sharon G.; Stephan, Paula E.; Winkler, Anne E. (Management Science, 2010)
This study investigates the impact of information technology (IT) on productivity and collaboration patterns in academe. Our data combine information on the diffusion of two noteworthy innovations in IT—BITNET and the Domain Name System (DNS)—with career-history data on research-active life scientists. We analyzed a random sample of 3,114 research-active life scientists from 314 U.S. institutions over a 25-year period and find that the availability of BITNET on a scientist's campus has a positive effect on his or her productivity and collaborative network. Our findings also support the hypothesis of a differential effect of IT across subgroups of the scientific labor force. Women scientists and those working at nonelite institutions benefit more from the availability of IT in terms of overall research output and an increase in the number of new coauthors they work with than do men or individuals at elite institutions. These results suggest that IT is an equalizing force, providing a greater boost to productivity and more collaboration opportunities for scientists who are more marginally positioned in academe.